PENGEMBANGAN INDUSTRI PENGOLAHAN IKAN DITINJAU DARI PRODUKSI HASIL TANGKAPAN DI PPN PALABUHANRATU - Lubis, Ernani; Sumiati, Sumiati (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2012)
In fact, fish processing industry is very importance to support development a fishing port. It is the same with the case of territorial fishing port (PPN) of Palabuhanratu. So that a research to determine the condition of fish catch production that was able to support the development of fish processing industry, need to be done. A case study on the underdeveloped of fish processing industry in PPN Palabuhanratu was done. Data analysis using descriptive numerical projection of the catch by estimating the need for the development of fish processing industry. Processing type that exist in PPN Palabuhanratu and nowadays are the processing on fish freezing, fish boiling, fish salting, crisp chips, meatball fish and abon fish. Based on the result of projection, the best fish production prospective as raw material for fish processing industry are skipjack tunas, eastern little tuna, tunas, hairtails, shark, ponyfish, ray, Indo-Pacific marlin, scads and wolf herring. A preceding ten year period of 2008-2017, the production of skipjack tunas, eastern little tuna, tunas, ponyfish, Indo-Pacific marlin, scads and wolf herring tend to increase, while the others will decrease. The development of other types of processing industries can be done for freezing, canning, fillet, loin, surimi and nuggets fish.